Lowering hepatic venous pressure agent carvedilol versus variceal banding ligation for clinical outcomes of cirrhotic portal hypertension - Wei Z; Wei F; Shao Z; Su G; Qi X; Zhang Y (Dove Medical Press, 2018)
Zhen-gang Wei,1–3 Feng-xian Wei,1–3 Zi-wei Shao,1–3 Guo-hong Su,1–3 Xue-ping Qi,3 You-cheng Zhang1–3 1Department of General Surgery, Lanzhou University Second Hospital, Lanzhou 730030, China; 2Hepato-Biliary-Pancreatic Institute, Lanzhou University Second Hospital, Lanzhou 730030, China; 3Lanzhou University Second Clinical Medical College, Lanzhou University Second Hospital, Lanzhou University, Lanzhou 730030, China Objective: Carvedilol is nonselective beta-blocker with a mild anti-alpha-1-adrenergic effect. Several studies proposed improved hemodynamic effects of carvedilol compared with propanolol. Our study was to perform a systematic review and meta-analysis of randomized control trials comparing carvedilol with variceal banding ligation (VBL).Methods: Studies were searched on online databases MEDLINE, EMBASE(Ovid), the Cochrane Library, Chinese Wanfang Database, and China National Knowledge Infrastructure between January 2000 and May 2018. Incidence of bleeding and mortality were main outcome measures. Subgroup analysis and sensitivity analysis were conducted to ensure the robustness of pooled estimates.Results: Ten randomized control trials including 1,269 cirrhotic patients were chosen. Compared with VBL, carvedilol showed similar preventive efficacy of risk ratios (RRs) in variceal bleeding, and bleeding-related mortality over different follow-up periods from 6 months to 24 months. Also, significant differences between carvedilol and VBL in overall mortality and other causes of mortality were failed to be found. Carvedilol achieved a lower incidence of portal hypertension gastropathy in both 6 months (RR=0.49, 95% CI: 0.38–0.64, P<0.00001) and 12 months (RR=0.35, 95% CI: 0.26–0.47, P<0.00001). Two trials compared combination of carvedilol and VBL with VBL alone; however, the results failed to find an improved preventive efficacy of bleeding (RR=0.71, 95% CI: 0.15–3.30, P=0.67).Conclusion: Carvedilol is equivalent to invasive VBL for variceal bleeding prevention. It can be well tolerated and may be of benefit to portal hypertension gastropathy. However, available data during 24 months follow-up did not support a potential advantage of carvedilol for prognosis as a lowering hepatic venous pressure agent.Keywords: carvedilol, endoscopic ligation, VBL, variceal bleeding, cirrhosis, mortality